Science Process Skills and Critical Thinking Ability Assessed from Students' Gender - Darmaji, D; Astalini, A; Kurniawan, D. A.; Putri, W. A. (Jurnal Pendidikan Fisika Indonesia, 2022)
Science process skills and critical thinking are skills that are very important and must be possessed by students in the 21st century. The purpose of this study is to determine the scientific process and critical thinking skills in terms of gender and see whether there is a relationship between science process skills and critical thinking skills. student. This is because the researcher wants to see a comparison of the abilities of male and female students. This research is a type of quantitative research with a research design. The population of this study were students of SMAN 6 Batanghari and the samples used were students of class A and class B, totaling 80 students with a ratio of 50 female students and 30 male students. The sampling technique used is simple random sampling with the criteria of students who are in Accredited Schools A and Class XII students who have studied the latest direct material. The search instrument used was an observation sheet and a critical reflectance test sheet. The data analysis used is descriptive statistical analysis and deductive analysis. Based on the results obtained, it can be concluded that the science process skills and critical thinking skills of female students are higher than male students. besides that there is a high and positive relationship between students' critical thinking skills and students' critical thinking skills. Based on these results, this research can be useful for teachers, namely so that teachers can carry out learning that can develop and improve science process skills so that students' critical thinking skills can also increase. In addition, the benefits for students themselves are so that students are accustomed to using skills in the learning process and can provide critical solutions in solving problems.